The Values of Local Wisdom in the Jong Racing Tradition as a Means of Character Education for Students - Komalasari Rika; Sialagan Pittanauli; Turyani Ima; Zaitun Zaitun; Kurmalasari Tety (SHS Web of Conferences)
This research aims to describe the values of local wisdom embedded in the Jong racing tradition as a means of character education for students. Jong is an ancient sailing vessel originating from the island of Java and used by Javanese and Sundanese sailors, and in later centuries, it was adopted by Pegu (Mon ethnic group) and Malay sailors. The Jong racing competition is an annual event that is not only participated in by local residents but also by participants from other regions. This research employs a qualitative descriptive method with direct observation, in-depth interviews, and documentation studies. The research was conducted in Bintan Regency, specifically in Tembeling Tanjung Subdistrict, Teluk Bintan District. The research results show that the Jong racing tradition embodies character values such as cooperation, discipline, responsibility, perseverance, and spirituality.